2014
DOI: 10.1016/j.urology.2013.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Non–organ-confined Prostate Cancer When Perineural Invasion Is Found on Biopsy

Abstract: OBJECTIVE To more precisely define the risk of non–organ-confined (non-OC) prostate cancer among men with perineural invasion (PNI) identified on prostate biopsy. MATERIALS AND METHODS The Johns Hopkins radical prostatectomy database was queried for men with PNI reported on prostate biopsy. Patients with and without non-OC disease were compared for differences in preoperative clinical and pathologic characteristics, including three biopsy-based measures of tumor volume (number of cores with cancer, percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Our results showed that 30.5% of patients had PNI, while the incidence in other research ranged from 21.1 to 50.2% [ 13 , 27 30 ]. The variation between these studies may be associated with different patient groups or pathological criteria.…”
Section: Discussioncontrasting
confidence: 41%
“…Our results showed that 30.5% of patients had PNI, while the incidence in other research ranged from 21.1 to 50.2% [ 13 , 27 30 ]. The variation between these studies may be associated with different patient groups or pathological criteria.…”
Section: Discussioncontrasting
confidence: 41%
“…PNI in PNB was considered as an important criterion in the decisionmaking of active surveillance in several studies. Still, in these studies, PNI was associated with higher tumor volume, which did not indicate a poor prognosis (9)(10)(11). In an investigation performed by Walsh and Epstein in 1993, the authors reported that knowledge about the presence and extent of PNI in needle biopsy specimens might provide information about capsular penetration and aid in the decision-making process for nerve-sparing surgery (12).…”
Section: Discussionmentioning
confidence: 96%
“…Non-standardized detecting methods may have contributed to the differences in the reported incidences of PNI. In the majority of reports, H&E staining was used to assess PNI 4 15 16 17 18 19 . However, determination of PNI is difficult and tedious by H&E if nerve fibers are severely damaged by invading tumor cells or if the nerve fibers are too thin.…”
Section: Discussionmentioning
confidence: 99%